2007
DOI: 10.1016/j.physc.2007.03.364
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of thermal conductivity of disordered d-wave superconductors by impurity-induced local moments

Abstract: The low-temperature thermal conductivity κ0/T of d-wave superconductors is generally thought to attain a "universal" value independent of disorder at sufficiently low temperatures, providing an important measure of the magnitude of the gap slope near its nodes. We discuss situations in which this inference can break down because of competing order, and quasiparticle localization. Specifically, we study an inhomogeneous BCS mean field model with electronic correlations included via a Hartree approximation for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…For YBCO such effects are absent since the disorder potential in the CuO 2 planes is negligible and independent of doping. This result agrees with a recently proposed origin of the unusual transport measurements in LSCO compared to YBCO [19,20].…”
supporting
confidence: 93%
“…For YBCO such effects are absent since the disorder potential in the CuO 2 planes is negligible and independent of doping. This result agrees with a recently proposed origin of the unusual transport measurements in LSCO compared to YBCO [19,20].…”
supporting
confidence: 93%
“…Other recent studies relevant to this phase have examined the more disordered, or more correlated state where such magnetic droplets are spontaneously formed around defects in zero field, and shown that they can indeed affect macroscopic observables such as NMR, thermal conductivity and superfluid density ͑T͒. [44][45][46][47][48][49] The physical picture of the ground state, that of an inhomogeneous mixture of AF droplets carrying net moments near the defect, is quite similar in our case. By working in the regime where moments are smaller and the effect of the field is larger, however, we hope to explain some of the observed puzzling aspects of the magnetoresistance.…”
Section: Introductionsupporting
confidence: 59%
“…Here, we investigate the effects on κ(T ) by local impurity-induced moments relevant e.g. to the underdoped regime of La 2−x Sr x CuO 4 (LSCO) [11,12,13]. Such moments are formed in the presence of background Hubbard interactions in the host material [14].…”
mentioning
confidence: 99%
“…For d-wave superconductors, a real-space BdG calculation of κ(T ) was used to study both localization phenomena [9,13] and the vortex state [30]. Here we follow the same approach but focus on the correlation effects and the role of disorder-induced magnetization using a realistic band structure for cuprate superconductors.…”
mentioning
confidence: 99%